The association between smoking behaviour and degenerative diseases - Simarmata, Gracia Imanuela; Hartono, Hartono; Sihotang, Widya Yanti; Tobing, Andrico Napolin Lumban; Dharma, Surya; Mylano, Tri Adi; Setiawan, Deni; Willano, Almira; Novianti, Desi; Suwanto, Denny; Haryadi, Haryadi; Mukhtar, Zulfikri; Kunardi, Sidharta; Reza, Faisal (Buletin Kedokteran & Kesehatan Prima, 2025)
Degenerative diseases represent a leading global cause of death, imposing a substantial health burden, wherein behavioural factors such as smoking are posited to play a significant role. This study aimed to analyse the association between smoking behaviour and the incidence of various degenerative diseases through a systematic literature review. The methodology employed was a systematic literature review, with article searches conducted across Google Scholar, PubMed, and Scopus databases from May to June 2025. Inclusion criteria encompassed full-text articles in Indonesian or English, published between 2020 and 2025, focusing on the association between smoking and degenerative diseases (hypertension, diabetes, stroke, kidney failure, cancer). From 230 identified articles, 15 met the criteria and were analysed. The synthesis of results demonstrated a significant association between smoking behaviour and an increased risk of degenerative diseases. Active smokers exhibited a three-fold higher risk of hypertension (OR=3.445), a twelve-fold higher risk of type 2 diabetes mellitus (OR=12.747), and a greater risk of developing cancer (lung, breast, laryngeal), stroke, and chronic kidney disease (CKD). Exposure to secondhand smoke among passive smokers also increased the risk of breast cancer nearly fourfold (OR=3.778). Underlying mechanisms include oxidative damage, chronic inflammation, endothelial dysfunction, and metabolic dysregulation. It is concluded that smoking is a major modifiable risk factor for degenerative diseases. Strengthening tobacco control policies, intensive health education, and smoking cessation programmes are required as primary prevention strategies.